Development of an IoT-Based Smart Home Prototype Using the Blynk Application - Adi Pramana, I Gusti Bagus; Akbar, Lalu A. Syamsul Irfan; Ramadhani, Cipta (Indonesian Mechanical Electrical and Industrial Research Society (IMEIRS), 2025)
The advancement of Internet of Things (IoT) technology has enabled the development of smart home automation systems that enhance comfort, security, and energy efficiency. This study aims to design, develop, and evaluate an IoT-based smart home prototype utilizing the Blynk App for remote monitoring and control. The system consists of various components, including an ESP32 microcontroller, relays, and an LDR sensor, which facilitate both automatic and manual light control. A prototype development approach was employed, encompassing system design, implementation, and testing. The experimental results demonstrate that the smart home prototype operates efficiently, with an average response time of 73.4 ms, indicating fast and reliable system performance. The integration of Blynk Cloud security protocols further ensures secure device communication and real-time monitoring. This research provides a functional smart home prototype that can serve as a foundation for future smart home innovations. Moreover, the system's ability to optimize energy usage and improve user convenience highlights its potential impact on sustainable living and smart home advancements.